Respuesta :
If you would like to solve (x – 3)(x + 9) = –27, you can do this using the following steps:
(x – 3)(x + 9) = –27
x^2 + 9x - 3x - 27 = -27
x^2 + 6x - 27 + 27 = 0
x^2 + 6x = 0
x * (x + 6) = 0
1. x = 0
2. x = -6
The correct result would be x = 0.
(x – 3)(x + 9) = –27
x^2 + 9x - 3x - 27 = -27
x^2 + 6x - 27 + 27 = 0
x^2 + 6x = 0
x * (x + 6) = 0
1. x = 0
2. x = -6
The correct result would be x = 0.
By evaluating the quadratic expression at each real number, we conclude that x = 0 is a solution (root) to (x - 3) · (x + 9) = -27. (Correct choice: C)
How to find the roots of a given polynomic expression
In this question we must find a solution for a polynomic expression. There are several approaches to find them. Since we have a polynomic expression as a product of binomials, we can determine the solution by evaluating at each choice:
x = 0
(0 - 3) · (0 + 9) = -27
(-3) · 9 = -27
-27 = -27
By evaluating the quadratic expression at each real number, we conclude that x = 0 is a solution (root) to (x - 3) · (x + 9) = -27. (Correct choice: C)
To learn more on quadratic functions: https://brainly.com/question/5975436
#SPJ5